- #1

- 15

- 0

## Homework Statement

a)

^{n}Ʃr

^{2}(r-1)

_{r=1}

## Homework Equations

Using the summation series formulae...

## The Attempt at a Solution

So far I have got:

r

^{2}(r-1) = r

^{3}-r

^{2}

Ʃr

^{3}= [itex]\frac{1}{4}[/itex]n

^{2}(n+1)

^{2}

Ʃr

^{2}= [itex]\frac{1}{6}[/itex]n(n+1)(2n+1)

Therefore,

Ʃr

^{3}-r

^{2}= [itex]\frac{1}{4}[/itex]n

^{2}(n+1)

^{2}- [itex]\frac{1}{6}[/itex]n(n+1)(2n+1)

But how do I subtract these two massive things from each other?!?!

Thanks.